Community Empowerment through the Development of Instant Herbal Beverage from Butterfly Pea Flower Using Foam-Mat Drying Technique - Septariawulan Kusumasari; Bayu Meindrawan; Aulia Ikhsan; Vega Yoesepa Pamela; Fandy Achmad; Najwa Rizkia; Salma Nur Haniyah; Nadia Nurfadilah Putri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The innovation of functional food products from local natural resources is one way to promote rural entrepreneurship and address food security. This community service activity aimed to empower the Kelompok Tani Kadugemblo by developing instant herbal drinks from butterfly pea (Clitoria ternatea) using the foam mat drying method. This program reached 50 individuals and comprised socialization, training, demonstrations, sensory analysis, and support with branding and packaging. The functional beverages, formulation, drying, and technology concepts were assessed using a pre- and post-test surrounding the participants’ knowledge. The mean pre-test score was 49.4%, while the post-test mean increased to 97.8%, resulting in a relative increase of 97.98%. These results indicate that the participatory and pragmatic approach strongly reinforced farmers’ knowledge and skills in producing instant beverage powders. It also increased understanding of the product, its attributes, the importance of shelf life, and the potential market for functional herbal drinks. This case study exemplifies the role of functional technology in fostering sustainable community development and rural economic growth.